2006
DOI: 10.1016/j.adolescence.2006.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts among indigenous Sami adolescents and majority peers in Arctic Norway: Prevalence and associated risk factors

Abstract: The prevalence of suicide attempts and associated risk factors such as sociodemographic conditions, emotional/behavioural problems and parent–child relationships were examined among 591 indigenous Sami and 2100 majority adolescents in Arctic Norway. There were no significant ethnic differences in prevalence of suicide attempts. In both ethnic groups, suicidal ideation, anxious/depressed problems and eating behaviour problems were associated with suicide attempts. Cross‐cultural differences in risk factors asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 35 publications
2
29
2
2
Order By: Relevance
“…Additionally, other studies have shown positive associations between smoking and SI (Gartrell et al, 1993) and SA (Chino & Fullerton-Gleason, 2006;Freedenthal & Stiffman, 2004;Gartrell et al, 1993;Silviken & Kvernmo, 2007) in bivariate and some multivariate analyses.…”
Section: Substance Usementioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, other studies have shown positive associations between smoking and SI (Gartrell et al, 1993) and SA (Chino & Fullerton-Gleason, 2006;Freedenthal & Stiffman, 2004;Gartrell et al, 1993;Silviken & Kvernmo, 2007) in bivariate and some multivariate analyses.…”
Section: Substance Usementioning
confidence: 99%
“…Several studies examining the association between age and suicidal behaviour in indigenous adolescents have failed to find a relationship (Chino & Fullerton-Gleason, 2006;Manson et al, 1989;Silviken & Kvernmo, 2007;Yuen et al, 1996). However, a few studies have reported some findings.…”
Section: Individual Factors Sociodemographic Variablesmentioning
confidence: 99%
See 3 more Smart Citations